2006
DOI: 10.1080/10408410601023516
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Homogenization as a Non-Thermal Technique for the Inactivation of Microorganisms

Abstract: In the pharmaceutical, cosmetic, chemical, and food industries high-pressure homogenization is used for the preparation or stabilization of emulsions and suspensions, or for creating physical changes, such as viscosity changes, in products. Another well-known application is cell disruption of yeasts or bacteria in order to release intracellular products such as recombinant proteins. The development over the last few years of homogenizing equipment that operates at increasingly higher pressures has also stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(145 citation statements)
references
References 78 publications
4
140
1
Order By: Relevance
“…Process parameters such as operating pressure, number of passes, suspension temperature and homogenizer valve design must be carefully scrutinized for efficient disruption [46][47]. It was reported that less efficient recovery of P(3HB) from A. latus was obtained with homogenizer compared to bead mill disruption due to severe micronization [23].…”
Section: High Pressure Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Process parameters such as operating pressure, number of passes, suspension temperature and homogenizer valve design must be carefully scrutinized for efficient disruption [46][47]. It was reported that less efficient recovery of P(3HB) from A. latus was obtained with homogenizer compared to bead mill disruption due to severe micronization [23].…”
Section: High Pressure Homogenizationmentioning
confidence: 99%
“…Process parame-ters are not the only factors that influence the cell disruption but microbial physiological parameters, namely type and growth phase of the microorganisms as well as cell concentration also affect the disruption efficiency (Table 2). Generally, Gram-positive bacteria are more difficult to be disrupted compared to Gram-negative bacteria [47]. Among the drawbacks associated with high pressure homogenization include the possibility of thermal degradation of desired products [48] and formation of fine cellular debris that would interfere with the further downstream processing of PHA granules [46].…”
Section: High Pressure Homogenizationmentioning
confidence: 99%
“…Floury et al [28] therefore attributes this to the viscous stress that have been caused by the high velocity of the fluid flow which is then impinging on the ceramic valve of the homogenizer, leading to the dissipation of a significant fraction of the mechanical energy as heat in the fluid. Considering pressure, temperature and number of passes (cycle) as the main parameters that affect fluid flow in HPH, Diels and Michiels [29] reiterated the level of microbial inactivation caused by the application of high-pressure homogenization increases with the pressure level which is similar with the high hydrostatic pressure (HHP) processes. Other underlying factors of considerable importance which have also been analyzed; authors have suggested a correlation between cell wall structure and high-pressure resistance between the microorganisms and HPH.…”
Section: Introductionmentioning
confidence: 99%
“…Cell disruption is considered as the isolation and preparation of intercellular products which is important for use in research and in the industries for manufacturing end products for consumers. In the industries, HPH application is linked to the production of stable emulsions, hence it is widely used in such areas [14,27,[29][30] apart from it being able to emulsify and disrupt particles into disperse phase of suspension, it has also extensively proven to be suitable for the inactivation of the microbial flora occurring in fruit juices and milk-based beverages [31] especially contributing to the preservation of the freshness and texture attributes, coupled with antioxidant capacity and polyphenols, vitamins and flavonoids content of the product [32]. Viscosity is another parameter also considered as a yardstick for the effectiveness of microbial organisms and this is dependent on the associated viscous stress of the material as well as the shear stresses and the concentration of liquid.…”
Section: Introductionmentioning
confidence: 99%
“…e inactivation kinetics for most microorganisms appear to be first order with respect to the applied pressure, in the range of HPH and UHPH pressure levels (100-350 MPa) [64]. In contrast, for repeated HPH passes, an asymptotic behavior is generally observed, which can be attributed to the natural distribution of individual cell resistance to pressure [65].…”
Section: Microbial Food Safetymentioning
confidence: 96%